Preoperative preparation workshop reduces postoperative maladaptive behavior in children. Issue 10 (12th June 2015) - Hilly, Julie; Hörlin, Anne‐Laure; Kinderf, Joelle; Ghez, Cecile; Menrath, Sabrina; Delivet, Honorine; Brasher, Christopher; Nivoche, Yves; Dahmani, Souhayl; Bosenberg, Adrian
Summary Introduction Postoperative maladaptive behaviors (POMBs) are common following pediatric anesthesia, and preoperative anxiety is associated with POMBs. A family‐centered preoperative preparation workshop was instituted with the aim of reducing the incidence of POMB and preoperative anxiety, and the study was constructed to evaluate its effectiveness. Material and methods A prospective cohort study was constructed, comparing patients who attended the workshop (workshop group) with patients who did not attend and who were matched for age and type of surgery (comparison group). Preoperative anxiety was measured using the mYPAS score, postoperative emergence agitation (EA) was measured using the PAED score, POMBs were assessed with the Post‐Hospital Behavior Questionnaire (PHBQ) on postoperative day 7, and PACU morphine consumption and PACU length of stay were recorded. Statistical analysis was performed employing the X² test, the Fisher's exact test, and the Mann–Whitney test as appropriate. Data were expressed as median [minimum, maximum]. Results Fifty‐six patients from 3 to 18 years of age were recruited. Twenty‐seven patients in the workshop group were compared to 26 in the comparison group, after exclusions for missing data. Significant differences were demonstrated between groups for POMBs intensity (PHBQ score 2 [0; 9] vs 5 [0; 10], P = 0.008) and incidence (PHBQ score >6: 3.6% vs 35.7%, P = 0.003), and for mYPAS score (28 [23; 87] vs 37 [23;100], P = 0.015). No difference was found for EA, PACU morphine consumption, or PACU length of stay. Conclusion The workshop appears to result in reduced preoperative anxiety and POMBs.